Media representations of the term ‘elderly’: a corpus-assisted discourse analysis in mainland and Hong Kong newspapers - Hong Meng; Azianura Hani Binti Shaari; Lay Shi Ng (Cogent Social Sciences)
China’s large and rapidly ageing population has drawn extensive media coverage. Based on corpus-assisted critical discourse analysis, this study collected 56 news articles from China Daily and 60 from South China Morning Post containing the term ‘elderly’ throughout 2023 to compare how this term is represented in mainland and Hong Kong media outlets. Results show that China Daily mentions the term ‘elderly’ 1.16 times more often than the South China Morning Post. The unique collocates, such as ‘elderly couples’, ‘elderly travelers’, and ‘elderly consumers’ in China Daily, construct older adults as active and contributing members of society. China Daily aligns with state-led inclusive efforts, emphasising broader ageing issues such as rural support and meal programs. At the same time, the South China Morning Post frames older adults as a critical urban challenge, focusing on housing shortages, transportation, and suicide in Hong Kong. These linguistic and thematic differences might be attributed to the distinct media systems and the broader historical and socio-political contexts in which each outlet operates.